Effect of using reporting guidelines during peer review on quality of final manuscripts submitted to a biomedical journal: masked randomised trial. (22nd November 2011) - Cobo, E; Cortés, J; Ribera, J M; Cardellach, F; Selva-O'Callaghan, A; Kostov, B; García, L; Cirugeda, L; Altman, D G; González, J A; Sànchez, J A; Miras, F; et al.
Abstract : Objective To investigate the effect of an additional review based on reporting guidelines such as STROBE and CONSORT on quality of manuscripts. Design Masked randomised trial. Population Original research manuscripts submitted to the Medicina Clínica journal from May 2008 to April 2009 and considered suitable for publication. Intervention Control group: conventional peer reviews alone. Intervention group: conventional review plus an additional review looking for missing items from reporting guidelines. Outcomes Manuscript quality, assessed with a 5 point Likert scale (primary: overall quality; secondary: average quality of specific items in paper). Main analysis compared groups as allocated, after adjustment for baseline factors (analysis of covariance); sensitivity analysis compared groups as reviewed. Adherence to reviewer suggestions assessed with Likert scale. Results Of 126 consecutive papers receiving conventional review, 34 were not suitable for publication. The remaining 92 papers were allocated to receive conventional reviews alone (n=41) or additional reviews (n=51). Four papers assigned to the conventional review group deviated from protocol; they received an additional review based on reporting guidelines. We saw an improvement in manuscript quality in favour of the additional review group (comparison as allocated, 0.25, 95% confidence interval –0.05 to 0.54; as reviewed, 0.33, 0.03 to 0.63). More papers with additional reviews than with conventional reviews alone improved from baseline (22 (43%) v eight (20%), difference 23.6% (3.2% to 44.0%), number needed to treat 4.2 (from 2.3 to 31.2), relative risk 2.21 (1.10 to 4.44)). Authors in the additional review group adhered more to suggestions from conventional reviews than to those from additional reviews (average increase 0.43 Likert points (0.19 to 0.67)). Conclusions Additional reviews based on reporting guidelines improve manuscript quality, although the observed effect was smaller than hypothesised and not definitively demonstrated. Authors adhere more to suggestions from conventional reviews than to those from additional reviews, showing difficulties in adhering to high methodological standards at the latest research phases. To boost paper quality and impact, authors should be aware of future requirements of reporting guidelines at the very beginning of their study. Trial registration and protocol Although registries do not include trials of peer review, the protocol design was submitted to sponsored research projects (Instituto de Salud Carlos III, PI081903).